A szerb Vajdaság, mint politikai cél/eszme kialakulása, formálódása, s a róla folyó diskurzusok 1848 és 1867 között - Pap, Tibor (Közép-Európai Közlemények, 2009)
As an implicit consequence of the set of Habsburg-granted privileges, Voivodina as a political-geographical category appeared in the political discourse of Southern Slavs in Hungary (especially of the Serbs) even before the 1848 revolution. However, the concept’s actual shape owes much to the ‘Skupština’ (assembly) in 1848 May. It appears in the 3. request towards the Court as an initiative built from below, aimed at creating regionalism. This initiative was meant to function as a pivotal point to the supposed trend of federalisation of the empire. Following these and after the supression of the revolution, during the absolutist times, Serbian Voivodina (along with the Temes Bánság) became a from-top forced, regionalisating concept, symbolising the mutual displeasure of both concerned parties. Existing as an emptied geographical construct of the Court, neither the ‘beneficients’ nor the ‘victims’ of this form were content with it. Following its abolishment, from 1861 to the Conciliation, both parties expressed arguments about its ‘rounding out’ (by redefining the counties on a nationality basis), about it being unacceptable or inevitable. With regard to the sensitivity of the Hungarian side, the term Voivodina itself is hardly mentioned in writings of the era... The present work intends to list and systematize the approaches mentioned, also to discover the (even today influential) roots of political-theo-retical thinking about the region. The issue has hardly lost its importance even to the present day, though positions have shifted substantially (radically).